Multipurpose hydrogenation catalyst as well as preparation method and application thereof

By designing a multi-purpose hydrogenation catalyst composed of copper oxide, nickel oxide, cerium oxide, titanium oxide and alumina, the problem of single function of the existing catalyst is solved, and the effect of efficient catalyzing of multiple hydrogenation reactions is achieved, and the effect of efficient catalyzing of multiple hydrogenation reactions is reduced. Production cost.

CN119158584APending Publication Date: 2024-12-20SHANDONG CHAMBROAD PETROCHEMICALS CO LTD

Patent Information

Application Number
CN202411299983.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing hydrogenation catalyst has a single function and limited applicability, making it difficult to be suitable for multiple hydrogenation reactions.

Method used

A multi-purpose hydrogenation catalyst is designed, consisting of copper oxide, nickel oxide, cerium oxide, titanium oxide and alumina. Through specific component ratios and preparation methods, the high hydrogenation performance and wide applicability of the catalyst are achieved. It is especially suitable for hydrogenation reactions of carbon-carbon double bonds and carbon-oxygen double bonds.

Benefits of technology

It achieves high hydrogenation performance and wide applicability of the catalyst, can effectively catalyze the hydrogenation reaction of various materials such as olefins, aromatics, aldehydes and enales, and is composed of non-precious metals, with low production costs and simple preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005047342280000131
    Figure BDA0005047342280000131
  • Figure BDA0005047342280000141
    Figure BDA0005047342280000141
  • Figure BDA0005047342280000151
    Figure BDA0005047342280000151
Patent Text Reader

Abstract

The invention provides a hydrogenation catalyst. The hydrogenation catalyst is prepared from copper oxide, nickel oxide, cerium oxide, titanium oxide and aluminum oxide, in the hydrogenation catalyst, the mass content of copper oxide is 8-25%; the mass content of nickel oxide is 19%-30%; the mass content of cerium oxide is 1%-5%; the mass content of titanium oxide is 1%-5%; the mass content of the aluminum oxide is 35-71%. According to the catalyst provided by the invention, CuO and NiO are taken as active components, CeO2 is taken as an auxiliary active component, mutual cooperation of copper and nickel bimetals is realized, and auxiliary catalysis of CeO2 is assisted, so that the catalyst is high in hydrogenation activity and wide in application range, and is particularly suitable for hydrogenation of carbon-carbon double bonds and carbon-oxygen double bonds. In addition, the catalyst is composed of non-noble metal, the production cost is low, the preparation process is simple, and industrial application is easy to achieve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and relates to a hydrogenation catalyst and a preparation method and application thereof, and in particular to a multi-purpose hydrogenation catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogenation technology is an important means to produce clean, high-purity compounds, among which efficient and high-performance hydrogenation catalysts are the core of hydrogenation technology. At present, the research and development of hydrogenation catalysts not only focuses on exploring new active components and carriers, but also optimizes the synergistic effects between active metals and between active metals and carriers by adding co-catalysts based on traditional active component systems and carriers, thereby improving the hydrogenation performance of the catalyst, realizing multiple uses of a hydrogenation catalyst, and improving the applicability of hydrogenation catalysts is also one of the directions of hydrogenation catalyst research and development.

[0003] Moreover, based on different materials, their structural compositions are different, and the functional requirements for hydrogenation catalysts will also be different, so it is extremely challenging to develop high-performance hydrogenation catalysts with strong applicability and multiple uses. For example, patent CN112547114 discloses an olefin hydrogenation catalyst, the nickel content of the catalyst is 7.5% to 15%, and the auxiliary agent is one or more of the first main group or lanthanide series, with a content of 0.1% to 1%, which is suitable for C2 to C4 olefin hydrogenation; patent CN113713817A discloses a nickel-based catalyst for catalyzing propionaldehyde hydrogenation to n-propanol, the main active component of the catalyst is Ni, the metal auxiliary agent is selected from one or more of Mg, Na, Ca, Co or Ba metal elements, the carrier material is selected from one or more of diatomaceous earth, white carbon black, MCM-41, SiO2 microspheres, SiO2 nanoparticles or SBA-15, and the catalyst is suitable for the hydrogenation of propionaldehyde. Although the hydrogenation catalysts disclosed in the above prior art have good performance, the function of the catalyst is single and the use is limited.

[0004] Therefore, how to design a more suitable multi-purpose hydrogenation catalyst that can be used in a variety of hydrogenation reactions and solve the above-mentioned problems of existing catalysts has become one of the focuses of widespread attention of many forward-looking researchers in the industry. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a hydrogenation catalyst and its preparation method and application, in particular a multi-purpose hydrogenation catalyst. The catalyst designed by the present invention has a high hydrogenation performance, which can be used for the hydrogenation of carbon-carbon double bonds, and can also be used for the hydrogenation of carbon-oxygen double bonds, and is particularly suitable for the hydrogenation of olefins, aromatics, aldehydes and alkenes.

[0006] The present invention provides a hydrogenation catalyst, which is composed of copper oxide, nickel oxide, cerium oxide, titanium oxide and aluminum oxide;

[0007] In the hydrogenation catalyst, the mass content of copper oxide is 8% to 25%;

[0008] The mass content of nickel oxide is 19% to 30%;

[0009] The mass content of cerium oxide is 1% to 5%;

[0010] The mass content of titanium oxide is 1% to 5%;

[0011] The mass content of aluminum oxide is 35% to 71%.

[0012] Preferably, the hydrogenation catalyst is a hydrogenation catalyst for hydrogenation of carbon-carbon double bonds and / or carbon-oxygen double bonds;

[0013] The hydrogenation catalyst specifically comprises a carrier composed of aluminum oxide and titanium oxide, and main active components of nickel oxide and copper oxide, and a secondary active component of cerium oxide, which are composited on the carrier;

[0014] The carrier comprises a porous carrier;

[0015] The hydrogenation catalyst is a hydrogenation catalyst that needs to be reduced and activated before use.

[0016] The present invention provides a method for preparing a hydrogenation catalyst as described in any one of the above technical solutions, comprising the following steps:

[0017] 1) mixing an aluminum source, a titanium source, a cerium source, an additive and an acid solution, and forming, drying and calcining to obtain a carrier;

[0018] 2) premixing a portion of the copper source, a portion of the nickel source and water to obtain a first mixed solution, and then placing the carrier obtained in the above step in the first mixed solution for a first impregnation, and then performing a first calcination to obtain a semi-finished product;

[0019] 3) The remaining copper source, the remaining nickel source and water are mixed again to obtain a second mixed solution, and the semi-finished product obtained in the above steps is placed in the second mixed solution for a second impregnation, and then calcined for a second time to obtain a hydrogenation catalyst.

[0020] Preferably, the aluminum source is selected from pseudo-boehmite and / or aluminum hydroxide dry gel;

[0021] The titanium source is selected from metatitanic acid and / or TiO2;

[0022] The cerium source is selected from cerium oxide;

[0023] The auxiliary agent is selected from sesbania powder;

[0024] The acid is selected from one or more of nitric acid, citric acid and malic acid.

[0025] Preferably, the additive is added in an amount of 1.5% to 5.5% of the total mass of the aluminum source, the cerium source and the titanium source;

[0026] The amount of the acid added is 0.05% to 7.5% of the total mass of the aluminum source, the cerium source and the titanium source;

[0027] The specific steps of the mixing are: firstly mixing the aluminum source, the titanium source, the cerium source and the auxiliary agent, and then adding the acid solution to continue mixing;

[0028] In the step 1), the heating rate of the calcination is 2 to 5°C / min;

[0029] In the step 1), the calcination temperature is 470-580°C;

[0030] In the step 1), the calcination time is 2 to 9 hours.

[0031] Preferably, the specific process of drying in step 1) is: drying at 60-80°C for 1-3 hours, and then drying at 105-120°C for 3-9 hours;

[0032] The heating rate of the first calcination is 2-5°C / min;

[0033] The temperature of the first calcination is 400-560°C;

[0034] The first calcination time is 2 to 8 hours.

[0035] Preferably, the copper source is selected from copper nitrate and / or copper acetate;

[0036] The nickel source is selected from nickel nitrate and / or nickel acetate;

[0037] The mass of the portion of the copper source accounts for 0.1% to 70% of the total mass of the copper source;

[0038] The mass of the part of nickel source accounts for 0.1% to 70% of the total mass of the nickel source;

[0039] The method further comprises a drying step before the first calcination and / or before the second calcination.

[0040] Preferably, the specific drying process before the first roasting and the second roasting is independently selected from: drying at 40-80°C for 1-10 hours, and then drying at 105-125°C for 3-5 hours;

[0041] The heating rate of the second calcination is 2-5°C / min;

[0042] The temperature of the second calcination is 400-560°C;

[0043] The second calcination time is 2 to 8 hours.

[0044] The present invention also provides the use of the hydrogenation catalyst described in any one of the above technical solutions or the hydrogenation catalyst prepared by the preparation method described in any one of the above technical solutions as a hydrogenation catalyst in the process of carbon-carbon double bond hydrogenation and / or carbon-oxygen double bond hydrogenation.

[0045] Preferably, the application is specifically to first reduce and activate the hydrogenation catalyst, and then perform the hydrogenation catalytic process;

[0046] The reduction activation method includes performing reduction activation under hydrogen conditions;

[0047] The volume ratio of hydrogen to hydrogenation catalyst is (100-2000) mL / h:1 mL;

[0048] The reduction activation temperature is 150-470°C;

[0049] The reduction activation time is 4 to 46 hours;

[0050] The heating rate of the reduction activation is 1-10°C / min.

[0051] The present invention provides a hydrogenation catalyst, which is composed of copper oxide, nickel oxide, cerium oxide, titanium oxide and aluminum oxide; in the hydrogenation catalyst, the mass content of copper oxide is 8% to 25%; the mass content of nickel oxide is 19% to 30%; the mass content of cerium oxide is 1% to 5%; the mass content of titanium oxide is 1% to 5%; the mass content of aluminum oxide is 35% to 71%. Compared with the prior art, the catalyst provided by the present invention uses CuO and NiO as active components and CeO2 as an auxiliary active component to achieve the mutual coordination of copper and nickel bimetallics, and is assisted by the auxiliary catalytic effect of CeO2, so that the catalyst has high hydrogenation activity and a wide range of applications, and is particularly suitable for the hydrogenation of carbon-carbon double bonds and carbon-oxygen double bonds. In addition, the catalyst is composed of non-precious metals, has low production costs, and a simple preparation process, and is easy to realize industrial application.

[0052] The catalyst provided by the invention has high hydrogenation performance, and can be used for hydrogenation of carbon-carbon double bonds, and can also be used for hydrogenation of carbon-oxygen double bonds, and is particularly suitable for hydrogenation of olefins, aromatics, aldehydes and olefins. DETAILED DESCRIPTION

[0053] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0054] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0055] There is no particular limitation on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials prepared with hydrogenation catalysts with conventional purity requirements.

[0056] All raw materials and process steps of the present invention, their brands or abbreviations are conventional brands or abbreviations in the art, and each brand or abbreviation is clear and definite in the field of its related use. Those skilled in the art can purchase them from the market or prepare them by conventional methods, or implement them with corresponding equipment according to the brands, abbreviations and corresponding uses.

[0057] The present invention provides a hydrogenation catalyst, which is composed of copper oxide, nickel oxide, cerium oxide, titanium oxide and aluminum oxide;

[0058] In the hydrogenation catalyst, the mass content of copper oxide is 8% to 25%;

[0059] The mass content of nickel oxide is 19% to 30%;

[0060] The mass content of cerium oxide is 1% to 5%;

[0061] The mass content of titanium oxide is 1% to 5%;

[0062] The mass content of aluminum oxide is 35% to 71%.

[0063] In the present invention, the mass content of copper oxide in the hydrogenation catalyst is 8% to 25%, can be 12% to 21%, or can be 16% to 17%.

[0064] In the present invention, the mass content of the nickel oxide is 19% to 30%, may be 21% to 28%, or may be 23% to 26%.

[0065] In the present invention, the mass content of the cerium oxide is 1% to 5%, can be 1.5% to 4.5%, or can be 2% to 4%.

[0066] In the present invention, the mass content of the titanium oxide is 1% to 5%, can be 1.5% to 4.5%, or can be 2% to 4%.

[0067] In the present invention, the mass content of the aluminum oxide is 35% to 71%, may be 40% to 65%, or may be 45% to 60%.

[0068] In the present invention, the hydrogenation catalyst is preferably a hydrogenation catalyst for hydrogenation of carbon-carbon double bonds and / or carbon-oxygen double bonds.

[0069] In the present invention, the hydrogenation catalyst is preferably a carrier composed of aluminum oxide and titanium oxide, and main active components of nickel oxide and copper oxide and auxiliary active component of cerium oxide are composited on the carrier.

[0070] In the present invention, the support preferably includes a porous support.

[0071] In the present invention, the hydrogenation catalyst is preferably a hydrogenation catalyst that needs to be reduced and activated before use.

[0072] In the present invention, the sum of the mass contents of the above components in the hydrogenation catalyst preferably satisfies 100%.

[0073] The present invention provides a method for preparing a hydrogenation catalyst as described in any one of the above technical solutions, comprising the following steps:

[0074] 1) mixing an aluminum source, a titanium source, a cerium source, an additive and an acid solution, and forming, drying and calcining to obtain a carrier;

[0075] 2) premixing a portion of the copper source, a portion of the nickel source and water to obtain a first mixed solution, and then placing the carrier obtained in the above step in the first mixed solution for a first impregnation, and then performing a first calcination to obtain a semi-finished product;

[0076] 3) The remaining copper source, the remaining nickel source and water are mixed again to obtain a second mixed solution, and the semi-finished product obtained in the above steps is placed in the second mixed solution for a second impregnation, and then calcined for a second time to obtain a hydrogenation catalyst.

[0077] The invention firstly mixes an aluminum source, a titanium source, a cerium source, an auxiliary agent and an acid solution, and then forms, dries and roasts the mixture to obtain a carrier.

[0078] In the present invention, the aluminum source is preferably selected from pseudo-boehmite and / or aluminum hydroxide dry gel, and more preferably pseudo-boehmite or aluminum hydroxide dry gel.

[0079] In the present invention, the titanium source is preferably selected from metatitanic acid and / or TiO2, more preferably metatitanic acid or TiO 2。

[0080] In the present invention, the cerium source is preferably selected from cerium oxide (CeO2).

[0081] In the present invention, the auxiliary agent is preferably selected from sesbania powder.

[0082] In the present invention, the acid is preferably selected from one or more of nitric acid, citric acid and malic acid, more preferably nitric acid and one of the above organic acids, more preferably nitric acid and citric acid.

[0083] In the present invention, the additive is preferably added in an amount of 1.5% to 5.5% of the total mass of the aluminum source, titanium source and cerium source, more preferably 2% to 5%, more preferably 2.5% to 4.5%, more preferably 3% to 4%.

[0084] In the present invention, the amount of the acid added is preferably 0.05% to 7.5% of the total mass of the aluminum source, the titanium source and the cerium source, more preferably 1% to 7%, and more preferably 2% to 6%.

[0085] In the present invention, the specific step of mixing is preferably to first mix the aluminum source, titanium source, cerium source and additive, and then add the acid solution to continue mixing.

[0086] In the present invention, the specific process of drying in the step 1) is preferably: drying at 60-80°C for 1-3 hours, then drying at 105-120°C for 3-9 hours, more preferably drying at 64-76°C for 1.4-2.6 hours, then drying at 108-117°C for 4-8 hours, more preferably drying at 68-72°C for 1.8-2.2 hours, then drying at 111-114°C for 5-7 hours.

[0087] In the present invention, in the step 1), the heating rate of calcination is preferably 2-5°C / min, more preferably 2.5-4.5°C / min, and more preferably 3-4°C / min.

[0088] In the present invention, in the step 1), the calcination temperature is preferably 470-580°C, more preferably 490-560°C, and more preferably 510-540°C.

[0089] In the present invention, in the step 1), the calcination time is preferably 2 to 9 hours, more preferably 3 to 8 hours, more preferably 4 to 7 hours, and more preferably 5 to 6 hours.

[0090] The present invention further premixes a portion of the copper source, a portion of the nickel source and water to obtain a first mixed solution, and then places the carrier obtained in the above steps into the first mixed solution for a first impregnation, and then performs a first roasting to obtain a semi-finished product.

[0091] In the present invention, the first calcination preferably further includes a drying step.

[0092] In the present invention, the specific process of drying before the first roasting is preferably: drying at 40-80°C for 1-10 hours, then drying at 105-125°C for 3-5 hours, more preferably drying at 45-75°C for 3-8 hours, then drying at 110-120°C for 3.4-4.6 hours, more preferably drying at 50-70°C for 5-6 hours, then drying at 114-115°C for 3.8-4.2 hours.

[0093] In the present invention, the heating rate of the first calcination is preferably 2 to 5°C / min, more preferably 2.5 to 4.5°C / min, and more preferably 3 to 4°C / min.

[0094] In the present invention, the temperature of the first calcination is preferably 400-560°C, more preferably 430-530°C, and more preferably 460-500°C.

[0095] In the present invention, the first calcination time is preferably 2 to 8 hours, more preferably 3 to 7 hours, and more preferably 4 to 6 hours.

[0096] In the present invention, the copper source is preferably selected from copper nitrate and / or copper acetate, more preferably copper nitrate or copper acetate.

[0097] In the present invention, the nickel source is preferably selected from nickel nitrate and / or nickel acetate, more preferably nickel nitrate or nickel acetate.

[0098] In the present invention, the mass of the portion of copper source preferably accounts for 0.1% to 70% of the total mass of the copper source, more preferably 10% to 55%, more preferably 30% to 55%, and specifically 55%.

[0099] In the present invention, the mass of the part of nickel source preferably accounts for 0.1% to 70% of the total mass of the nickel source, more preferably 10% to 55%, more preferably 30% to 55%, specifically 55%.

[0100] Finally, the present invention remixes the remaining copper source, the remaining nickel source and water to obtain a second mixed solution, and places the semi-finished product obtained in the above steps in the second mixed solution for a second impregnation, and then calcines it for a second time to obtain a hydrogenation catalyst.

[0101] In the present invention, the hydrogenation catalyst prepared by impregnation is prepared by a two-step method.

[0102] In the present invention, the second calcination preferably further includes a drying step.

[0103] In the present invention, the specific process of drying before the second calcination is preferably: drying at 40-80°C for 1-10 hours, then drying at 105-125°C for 3-5 hours, more preferably drying at 45-75°C for 3-8 hours, then drying at 110-120°C for 3.4-4.6 hours, more preferably drying at 50-70°C for 5-6 hours, then drying at 114-115°C for 3.8-4.2 hours.

[0104] In the present invention, the heating rate of the second calcination is preferably 2 to 5°C / min, more preferably 2.5 to 4.5°C / min, and more preferably 3 to 4°C / min.

[0105] In the present invention, the temperature of the second calcination is preferably 400-560°C, more preferably 430-530°C, and more preferably 460-500°C.

[0106] In the present invention, the second calcination time is preferably 2 to 8 hours, more preferably 3 to 7 hours, and more preferably 4 to 6 hours.

[0107] The present invention provides the use of the hydrogenation catalyst described in any one of the above technical solutions or the hydrogenation catalyst prepared by the preparation method described in any one of the above technical solutions as a hydrogenation catalyst in the process of carbon-carbon double bond hydrogenation and / or carbon-oxygen double bond hydrogenation.

[0108] In the present invention, the application is preferably to firstly reduce and activate the hydrogenation catalyst and then perform the hydrogenation catalytic process.

[0109] In the present invention, the reduction activation method preferably includes reduction activation under hydrogen conditions.

[0110] In the present invention, the volume ratio of hydrogen to hydrogenation catalyst is preferably (100-2000) mL / h:1 mL, more preferably (500-1600) mL / h:1 mL, and more preferably (900-1200) mL / h:1 mL. Specifically, the above volume ratio of the present invention means that when the catalyst is reduced, the amount of hydrogen that needs to be introduced into 1 mL of catalyst within 1 hour is 100-2000 mL.

[0111] In the present invention, the reduction activation temperature is preferably 150 to 470°C, more preferably 200 to 420°C, more preferably 250 to 370°C, and more preferably 300 to 320°C.

[0112] In the present invention, the reduction activation time is preferably 4 to 46 hours, more preferably 14 to 36 hours, and more preferably 24 to 26 hours.

[0113] In the present invention, the heating rate of the reduction activation is preferably 1 to 10° C. / min, more preferably 3 to 8° C. / min, and more preferably 5 to 6° C. / min.

[0114] In the present invention, after the catalyst undergoes a reduction process, the hydrogenation active components of the catalyst are Cu and Ni. The reduction process reduces copper oxide and nickel oxide to Cu and Ni, which then play a catalytic role. The co-catalyst CeO2 and the carriers TiO2 and Al2O3 are still in an oxidized state.

[0115] The present invention is to complete and refine the overall technical solution, better ensure the structure and composition of the hydrogenation catalyst, and further improve the hydrogenation performance and universality of the hydrogenation catalyst. The above-mentioned multi-purpose hydrogenation catalyst and its preparation method and application may specifically include the following contents:

[0116] A multi-purpose hydrogenation catalyst and a preparation method and application thereof.

[0117] A multi-purpose hydrogenation catalyst, which consists of CuO, NiO, CeO2, TiO2 and alumina; the catalyst is used for hydrogenation of carbon-carbon double bonds and / or carbon-oxygen double bonds.

[0118] Specifically, the mass percentage of CuO in the catalyst is 8% to 25%, the mass percentage of NiO is 19% to 30%, the mass percentage of CeO2 is 1% to 5%, the mass percentage of TiO2 is 1% to 5%, and the mass percentage of aluminum oxide is 35% to 71%.

[0119] A method for preparing a multi-purpose hydrogenation catalyst comprises the following steps:

[0120] a) Preparation of the carrier: The aluminum source, titanium source, cerium source, additive and acid solution are uniformly mixed and then formed, and then dried and calcined to obtain the carrier;

[0121] b) Catalyst preparation: The Cu source and the Ni source are fixed on the carrier obtained in step a), and the catalyst is obtained through drying and calcining.

[0122] Specifically, the drying process in step a) is as follows: drying at 60°C to 80°C for 1h to 3h, and then drying at 105°C to 120°C for 3h to 9h.

[0123] Specifically, the calcination process in step a) is as follows: heating to 470° C. to 580° C. at a heating rate of 2° C. / min to 5° C. / min and keeping the temperature for 2 h to 9 h.

[0124] Specifically, the drying process in step b) is as follows: drying at 40°C to 80°C for 1h to 10h, and then drying at 105°C to 125°C for 3h to 5h.

[0125] Specifically, the calcination process in step b) is: heating to 400° C. to 560° C. at a heating rate of 2° C. / min to 5° C. / min and keeping the temperature for 2 h to 8 h.

[0126] Specifically, the Cu source is one or more of copper nitrate or copper acetate.

[0127] Specifically, the Ni source is one or more of nickel nitrate or nickel acetate.

[0128] The application of the multi-purpose hydrogenation catalyst also includes: under hydrogen conditions, first reducing and activating the catalyst at a temperature of 150° C. to 470° C., and then introducing the material for catalytic reaction.

[0129] Specifically, the multi-purpose hydrogenation catalyst is applied to the hydrogenation of carbon-carbon double bonds and carbon-oxygen double bonds, and is particularly suitable for the hydrogenation of olefins, aromatics, aldehydes and alkenes.

[0130] The specific application process of the catalyst provided by the present invention includes: firstly reducing and activating the catalyst under hydrogen conditions, and then introducing materials to carry out catalytic reaction.

[0131] Specifically, the catalyst reduction conditions are: the volume ratio of hydrogen to catalyst is 100-2000:1 ml / mlh, the reduction pressure is normal pressure or slightly positive pressure (0.1-1.5 MPa), the reduction temperature is 150°C-470°C, the reduction time is 4-46h, and the heating rate is 1°C / min-10°C / min.

[0132] Furthermore,

[0133] The invention provides a multi-purpose hydrogenation catalyst and a preparation method and application thereof. The catalyst has excellent hydrogenation performance and wide application, and is suitable for the hydrogenation of carbon-carbon double bonds and carbon-oxygen double bonds, and is particularly suitable for the hydrogenation of olefins, aromatics, aldehydes and alkenals.

[0134] The present invention discloses a multi-purpose hydrogenation catalyst and a preparation method and application thereof, including:

[0135] The hydrogenation catalyst is composed of CuO, NiO, CeO2, TiO2 and alumina, and the content of each component is as follows: the mass percentage of CuO is 8% to 25%, the mass percentage of NiO is 19% to 30%, the mass percentage of CeO2 is 1% to 5%, the mass percentage of TiO2 is 1% to 5%, and the mass percentage of alumina is 35% to 71%.

[0136] Specifically, the mass percentage of CuO in the hydrogenation catalyst is 8% to 15%, the mass percentage of NiO is 19% to 25%, the mass percentage of CeO2 is 1% to 4%, the mass percentage of TiO2 is 1% to 3%, and the mass percentage of aluminum oxide is 53% to 71%.

[0137] The present invention also provides a method for preparing the above catalyst, comprising the following steps:

[0138] a) Preparation of the carrier: The aluminum source, titanium source, cerium source, additive and acid solution are uniformly mixed and then formed, and then dried and calcined to obtain the carrier;

[0139] b) Catalyst preparation: The Cu source and the Ni source are fixed on the carrier obtained in step a), and the hydrogenation catalyst is obtained through drying and calcining.

[0140] The present invention firstly mixes an aluminum source, a titanium source, a cerium source, an auxiliary agent and an acid solution uniformly and then forms the mixture, and then dries and roasts the mixture to obtain a carrier. In the present invention, the aluminum source is preferably selected from pseudo-boehmite and / or aluminum hydroxide dry gel; the present invention has no special restrictions on the source of the aluminum source, and commercially available products of the pseudo-boehmite and aluminum hydroxide dry gel known to those skilled in the art can be used.

[0141] Specifically, the titanium source is preferably selected from titanic acid and / or TiO2; the present invention has no special limitation on the source of the titanium source, and commercially available products of the above-mentioned titanic acid and TiO2 well known to those skilled in the art can be used.

[0142] Specifically, the cerium source is preferably selected from CeO2; the present invention has no special limitation on the source of the cerium source, and the commercially available CeO2 known to those skilled in the art can be used.

[0143] Specifically, the amounts of the aluminum source, cerium source and titanium source are preferably calculated according to the mass percentages of Al2O3, CeO2 and TiO2 in the catalyst.

[0144] Specifically, the auxiliary agent is preferably sesbania powder; the present invention has no special restrictions on the source of the auxiliary agent, and the commercially available sesbania powder known to those skilled in the art can be used. In the present invention, the addition amount of the auxiliary agent is preferably 1.5% to 5.5% of the total mass of the aluminum source, the cerium source, and the titanium source, preferably 2% to 4%.

[0145] Specifically, the acid solution is preferably a mixed solution of one or more of nitric acid, citric acid and malic acid, preferably a mixed solution of nitric acid and citric acid; the concentration of the nitric acid is preferably 65% ​​to 68%, and commercially available products well known to those skilled in the art can be used; the present invention has no special restrictions on the source of the citric acid, and commercially available products well known to those skilled in the art can be used; the present invention has no special restrictions on the source of the malic acid, and commercially available products well known to those skilled in the art can be used. In the present invention, the addition amount of the nitric acid is preferably 0.2% to 5% of the total mass of the aluminum source, cerium source, and titanium source; the addition amount of the citric acid is preferably 0.05% to 2.5% of the total mass of the aluminum source, cerium source, and titanium source; the addition amount of the malic acid is preferably 0.1% to 2% of the total mass of the aluminum source, cerium source, and titanium source.

[0146] Specifically, the process of uniformly mixing the aluminum source, cerium source, titanium source, auxiliary agent and acid solution is as follows: after mixing the aluminum source, cerium source, titanium source and auxiliary agent, the acid solution is added and uniformly mixed. The present invention has no particular limitation on the molding device, and an extruder well known to those skilled in the art can be used.

[0147] Specifically, the drying in step a) is: drying at 60°C to 80°C for 1h to 3h, and then drying at 105°C to 120°C for 3h to 9h; preferably, drying at 60°C to 80°C for 1h to 3h, and then drying at 105°C to 120°C for 3h to 5h.

[0148] Specifically, the calcination in step a) is: heating to 470°C-580°C at a heating rate of 2°C / min-5°C / min and keeping warm for 2h-9h; preferably heating to 480°C-560°C at a heating rate of 2°C / min-5°C / min and keeping warm for 2h-8h; preferably heating to 490°C-550°C at a heating rate of 2°C / min-5°C / min and keeping warm for 3h-6h.

[0149] Specifically, in step b), the Cu source and the Ni source are fixed on the carrier obtained in step a), and the fixing method is preferably impregnation.

[0150] Specifically, the impregnation is to divide the total mass of the Cu source and the Ni source into two impregnations, wherein the amount of the Cu source and the Ni source used in the first impregnation is 55% of the total mass of the Cu source and the Ni source, and the amount of the Cu source and the Ni source used in the second impregnation is 45% of the total mass of the Cu source and the Ni source.

[0151] Specifically, after the two impregnations are completed, drying and calcination treatments need to be performed in sequence, and the catalyst is obtained after the second calcination is completed.

[0152] Specifically, the drying in step b) is: drying at 40°C to 80°C for 1h to 10h, and then drying at 105°C to 125°C for 3h to 5h; preferably, drying at 40°C to 80°C for 4h to 7h, and then drying at 105°C to 125°C for 3h to 5h.

[0153] Specifically, the calcination in step b) is: heating to 400°C-560°C at a heating rate of 2°C / min-5°C / min and keeping warm for 2h-8h; preferably, heating to 430°C-550°C at a heating rate of 2°C / min-5°C / min and keeping warm for 4h-6h.

[0154] Specifically, the Cu source is one or more of copper nitrate and copper acetate. The present invention has no special limitation on the source of the Cu source, and commercially available copper nitrate and copper acetate known to those skilled in the art can be used.

[0155] Specifically, the Ni source is one or more of nickel nitrate and nickel acetate. The present invention has no special limitation on the source of the Ni source, and commercially available products of the nickel nitrate and nickel acetate known to those skilled in the art can be used.

[0156] Specifically, the catalyst of the present invention is used for the hydrogenation of carbon-carbon double bonds and carbon-oxygen double bonds, and is particularly suitable for the hydrogenation of olefins, aromatics, aldehydes and alkenals.

[0157] The catalyst provided by the present invention also comprises the following steps before application: firstly reducing and activating the catalyst under hydrogen conditions, and then introducing materials for catalytic reaction.

[0158] Specifically, the catalyst reduction activation conditions are: the volume ratio of hydrogen to catalyst is 100-2000:1ml / mlh, the reduction pressure is normal pressure or slightly positive pressure, such as 0.1Mpa~1.5MPa, the reduction temperature is 150℃~470℃, the reduction time is 4~46h, and the heating rate is 1℃ / min~10℃ / min; the preferred volume ratio of hydrogen to catalyst is 100-2000:1ml / mlh, the reduction pressure is 0.15~1.2MPa, the reduction temperature is 190℃~410℃, the reduction time is 4~18h, and the heating rate is 1℃ / min~8℃ / min; the preferred volume ratio of hydrogen to catalyst is 300-1200:1ml / mlh, the reduction pressure is 0.5~1.0MPa, the reduction temperature is 190℃~410℃, the reduction time is 4~12h, and the heating rate is 1℃ / min~6℃ / min.

[0159] The above content of the present invention provides a multi-purpose hydrogenation catalyst and its preparation method and application. The catalyst provided by the present invention uses CuO and NiO as active components and CeO2 as a co-active component to achieve the mutual coordination of copper and nickel bimetallics, and is supplemented by the co-catalytic effect of CeO2, so that the catalyst has high hydrogenation activity and a wide range of applications, and is particularly suitable for the hydrogenation of carbon-carbon double bonds and carbon-oxygen double bonds. In addition, the catalyst is composed of non-precious metals, has low production costs, and a simple preparation process, and is easy to realize industrial application.

[0160] The catalyst provided by the invention has high hydrogenation performance, and can be used for hydrogenation of carbon-carbon double bonds, and can also be used for hydrogenation of carbon-oxygen double bonds, and is particularly suitable for hydrogenation of olefins, aromatics, aldehydes and olefins.

[0161] In order to further illustrate the present invention, a hydrogenation catalyst provided by the present invention and its preparation method and application are described in detail below in combination with examples. However, it should be understood that these examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following examples.

[0162] Example 1

[0163] Catalyst preparation:

[0164] (1) 91.33 g of pseudo-boehmite (dry basis 75%), 1.226 g of metatitanic acid, 1.5 g of CeO2 and 2.822 g of sesbania powder were mixed evenly, and then 53 mL of a mixed acid solution containing 0.941 g of citric acid and 1.881 g of HNO3 (65%) was added and mixed evenly. The mixture was formed on an extruder, dried at 90°C for 3 h, and then dried at 110°C for 3 h. The mixture was then heated to 550°C in a muffle furnace at a heating rate of 5°C / min and calcined for 4 h to obtain a carrier.

[0165] (2) Weigh 81.759g Ni(NO3)2·6H2O and divide it into two parts, the first part is 55% Ni(NO3)2·6H2O and the second part is 45% Ni(NO3)2·6H2O. Weigh 24.298g Cu(NO3)2·3H2O and divide it into two parts, the first part is 55% Cu(NO3)2·3H2O and the second part is 45% Cu(NO3)2·3H2O. Prepare 52mL of aqueous solution of the first part Ni(NO3)2·6H2O and the first part Cu(NO3)2·3H2O, and then impregnate it on the support obtained in step 1). After the first impregnation, dry it in an oven at 50°C for 3h, then dry it at 105°C for 5h, and finally calcine it in a muffle furnace at 530°C for 5h to obtain a first impregnation catalyst. After obtaining the first impregnation catalyst, start the second impregnation, and mix the second part Ni(NO3)2·6H2O and the second part Cu(NO3)2·3H2O. Cu(NO3)2·3H2O was prepared into 52mL of aqueous solution, and then impregnated onto the first impregnation catalyst. After the second impregnation, it was first dried in an oven at 50°C for 3h, then dried at 105°C for 5h, and finally calcined in a muffle furnace at 530°C for 5h to obtain a hydrogenation catalyst. The content of each component was: CuO content 8wt%, NiO content 21wt%, CeO2 content 1.5wt%, Al2O3 content 68.5wt%, and TiO2 content 1wt%.

[0166] Catalyst Evaluation:

[0167] In a fixed bed reactor, the hydrogenation catalyst provided in Example 1 was used. Under hydrogen conditions, the catalyst was first reduced and activated: the hydrogen partial pressure was 0.5 MPa, the gas-to-agent ratio was 1000:1, the reduction temperature was 450°C, and the reduction time was 12 h; then the catalytic reactions were carried out: (1) mixed pentene (2-methyl-1-butene and 2-methyl-2-butene) hydrogenation: 30% mixed isopentene and 70% isooctane mixed raw material, (2) benzene hydrogenation: 7% benzene and isooctane mixed raw material, (3) mixed C6 aldehyde hydrogenation, and (4) mixed C12 olefin aldehyde hydrogenation.

[0168] Table 1 Hydrogenation results of the catalyst of Example 1 on different raw materials

[0169]

[0170] Example 2

[0171] Catalyst preparation:

[0172] The preparation method is the same as that of Example 1, but the contents of CuO and Al2O3 in the catalyst are adjusted.

[0173] (1) 86 g of pseudo-boehmite (dry basis 75%), 1.226 g of metatitanic acid, 1.5 g of CeO2 and 2.662 g of sesbania powder were mixed evenly, and then 50 mL of a mixed acid solution containing 0.887 g of citric acid and 1.775 g of HNO3 (65%) was added and mixed evenly. The mixture was formed on an extruder, dried at 90°C for 3 h, and then dried at 110°C for 3 h. The mixture was then heated to 550°C in a muffle furnace at a heating rate of 5°C / min and calcined for 4 h to obtain a carrier.

[0174] (2) Weigh 81.759g Ni(NO3)2·6H2O and divide it into two parts, the first part is 55% Ni(NO3)2·6H2O and the second part is 45% Ni(NO3)2·6H2O; weigh 36.447g Cu(NO3)2·3H2O and divide it into two parts, the first part is 55% Cu(NO3)2·3H2O and the second part is 45% Cu(NO3)2·3H2O. Prepare 49mL of aqueous solution of the first part Ni(NO3)2·6H2O and the first part Cu(NO3)2·3H2O, and then impregnate it on the carrier obtained in step 1). After the first impregnation, dry it in an oven at 50°C for 3h, then dry it at 105°C for 5h, and finally calcine it in a muffle furnace at 530°C for 5h to obtain a first impregnation catalyst; after obtaining the first impregnation catalyst, start the second impregnation, and mix the second part Ni(NO3)2·6H2O and the second part Cu(NO3)2·3H2O into 49mL of aqueous solution. u(NO3)2·3H2O was prepared into 49mL of aqueous solution, and then impregnated onto the once impregnated catalyst. After the second impregnation, it was first dried in an oven at 50°C for 3h, then dried at 105°C for 5h, and finally calcined in a muffle furnace at 530°C for 5h to obtain a hydrogenation catalyst. The contents of each component were: CuO content 12wt%, NiO content 21wt%, CeO2 content 1.5wt%, Al2O3 content 64.5wt%, and TiO2 content 1wt%.

[0175] Catalyst Evaluation:

[0176] The catalyst prepared in Example 2 was used, and the catalyst evaluation method was the same as that in Example 1. The results are shown in Table 2 below.

[0177] Table 2 Hydrogenation results of the catalyst of Example 2 on different raw materials

[0178]

[0179] Example 3

[0180] Catalyst preparation:

[0181] The preparation method is the same as that of Examples 1 and 2, except that the contents of CuO and Al2O3 in the catalyst are adjusted.

[0182] (1) 82 g of pseudo-boehmite (dry basis 75%), 1.226 g of metatitanic acid, 1.5 g of CeO2 and 2.542 g of sesbania powder were mixed evenly, and 48 mL of a mixed acid solution containing 0.847 g of citric acid and 1.695 g of HNO3 (65%) was added and mixed evenly. The mixture was formed on an extruder, dried at 90°C for 3 h, and then dried at 110°C for 3 h. The mixture was then heated to 530°C in a muffle furnace at a heating rate of 5°C / min and calcined for 4 h to obtain a carrier.

[0183] (2) Weigh 81.759g Ni(NO3)2·6H2O and divide it into two parts, the first part is 55% Ni(NO3)2·6H2O and the second part is 45% Ni(NO3)2·6H2O. Weigh 45.559g Cu(NO3)2·3H2O and divide it into two parts, the first part is 55% Cu(NO3)2·3H2O and the second part is 45% Cu(NO3)2·3H2O. Prepare 48mL of aqueous solution of the first part Ni(NO3)2·6H2O and the first part Cu(NO3)2·3H2O, and then impregnate it on the support obtained in step 1). After the first impregnation, dry it in an oven at 50°C for 3h, then dry it at 105°C for 5h, and finally calcine it in a muffle furnace at 530°C for 5h to obtain a first impregnation catalyst. After obtaining the first impregnation catalyst, start the second impregnation, and mix the second part Ni(NO3)2·6H2O and the second part Cu(NO3)2·3H2O into 48mL of aqueous solution. u(NO3)2·3H2O was prepared into 48mL of aqueous solution, and then impregnated onto the once impregnated catalyst. After the second impregnation, it was first dried in an oven at 50°C for 3h, then dried at 105°C for 5h, and finally calcined in a muffle furnace at 530°C for 5h to obtain a hydrogenation catalyst. The contents of each component were: CuO content 15wt%, NiO content 21wt%, CeO2 content 1.5wt%, Al2O3 content 61.5wt%, and TiO2 content 1wt%.

[0184] Catalyst Evaluation:

[0185] The catalyst prepared in Example 3 was used, and the catalyst evaluation method was the same as that in Example 1. The results are shown in Table 3 below.

[0186] Table 3 Hydrogenation results of the catalyst of Example 3 for different raw materials

[0187]

[0188] Example 4

[0189] Catalyst preparation:

[0190] The preparation method is the same as that of Example 2, but the contents of TiO2 and Al2O3 in the catalyst are adjusted.

[0191] (1) 83.33 g of pseudo-boehmite (dry basis 75%), 3.677 g of metatitanic acid, 1.5 g of CeO2 and 2.655 g of sesbania powder were mixed evenly, and then 50 mL of a mixed acid solution containing 0.885 g of citric acid and 1.770 g of HNO3 (65%) was added and mixed evenly. The mixture was formed on an extruder, dried at 90°C for 3 h, and then dried at 110°C for 3 h. The mixture was then heated to 530°C in a muffle furnace at a heating rate of 5°C / min and calcined for 4 h to obtain a carrier.

[0192] (2) Weigh 81.759g Ni(NO3)2·6H2O and divide it into two parts, the first part is 55% Ni(NO3)2·6H2O and the second part is 45% Ni(NO3)2·6H2O. Weigh 36.447g Cu(NO3)2·3H2O and divide it into two parts, the first part is 55% Cu(NO3)2·3H2O and the second part is 45% Cu(NO3)2·3H2O. Prepare the first part of Ni(NO3)2·6H2O and the first part of Cu(NO3)2·3H2O into 50mL aqueous solution, and then impregnate it onto the support obtained in step 1). After the first impregnation, dry it in an oven at 50℃ for 3h, then dry it at 105℃ for 5h, and finally calcine it in a muffle furnace at 530℃ for 5h to obtain a first impregnation catalyst. After obtaining the first impregnation catalyst, start the second impregnation, and mix the second part of Ni(NO3)2·6H2O and the second part of Cu(NO3)2·3H2O into 50mL aqueous solution. u(NO3)2·3H2O was prepared into a 50mL aqueous solution and then impregnated onto the once impregnated catalyst. After the second impregnation, it was first dried in an oven at 50°C for 3h, then dried at 105°C for 5h, and finally calcined in a muffle furnace at 530°C for 5h to obtain a hydrogenation catalyst. The contents of each component were: CuO content 12wt%, NiO content 21wt%, CeO2 content 1.5wt%, Al2O3 content 62.5wt%, and TiO2 content 3wt%.

[0193] Catalyst Evaluation:

[0194] The catalyst prepared in Example 4 was used, and the catalyst evaluation method was the same as that in Example 1. The results are shown in Table 4 below.

[0195] Table 4 Hydrogenation results of the catalyst of Example 4 on different raw materials

[0196]

[0197] Example 5

[0198] Catalyst preparation:

[0199] The preparation method is the same as that of Example 1, but the contents of TiO2 and Al2O3 in the catalyst are adjusted.

[0200] (1) After 90 g of pseudo-boehmite (dry basis 75%), 2.451 g of metatitanic acid, 1.5 g of CeO2 and 2.819 g of sesbania powder were mixed evenly, 52.6 mL of a mixed acid solution containing 0.940 g of citric acid and 1.879 g of HNO3 (65%) was added and mixed evenly, the mixture was formed on an extruder, dried at 90°C for 3 h, and then dried at 110°C for 3 h. The mixture was then heated to 530°C in a muffle furnace at a heating rate of 5°C / min and calcined for 4 h to obtain a carrier.

[0201] (2) Weigh 81.759g Ni(NO3)2·6H2O and divide it into two parts, the first part is 55% Ni(NO3)2·6H2O and the second part is 45% Ni(NO3)2·6H2O. Weigh 24.298g Cu(NO3)2·3H2O and divide it into two parts, the first part is 55% Cu(NO3)2·3H2O and the second part is 45% Cu(NO3)2·3H2O. Prepare 52mL of aqueous solution of the first part Ni(NO3)2·6H2O and the first part Cu(NO3)2·3H2O, and then impregnate it on the support obtained in step 1). After the first impregnation, dry it in an oven at 50°C for 3h, then dry it at 105°C for 5h, and finally calcine it in a muffle furnace at 530°C for 5h to obtain a first impregnation catalyst. After obtaining the first impregnation catalyst, start the second impregnation, and mix the second part Ni(NO3)2·6H2O and the second part Cu(NO3)2·3H2O. Cu(NO3)2·3H2O was prepared into 52mL of aqueous solution, and then impregnated onto the once impregnated catalyst. After the second impregnation, it was first dried in an oven at 50°C for 3h, then dried at 105°C for 5h, and finally calcined in a muffle furnace at 530°C for 5h to obtain a hydrogenation catalyst. The contents of each component were: CuO content 8wt%, NiO content 21wt%, CeO2 content 1.5wt%, Al2O3 content 67.5wt%, and TiO2 content 2wt%.

[0202] Catalyst Evaluation:

[0203] The catalyst prepared in Example 5 was used, and the catalyst evaluation method was the same as that in Example 1. The results are shown in Table 5 below.

[0204] Table 5 Hydrogenation results of the catalyst of Example 5 on different raw materials

[0205]

[0206] Example 6

[0207] Catalyst preparation:

[0208] The preparation method is the same as that of Example 5, but the contents of NiO and Al2O3 in the catalyst are adjusted.

[0209] (1) 92.67 g of pseudo-boehmite (dry basis 75%), 2.451 g of metatitanic acid, 1.5 g of CeO2 and 2.90 g of sesbania powder were mixed evenly, and then 54 mL of a mixed acid solution containing 0.966 g of citric acid and 1.932 g of HNO3 (65%) was added and mixed evenly. The mixture was formed on an extruder, dried at 90°C for 3 h, and then dried at 110°C for 3 h. The mixture was then heated to 530°C in a muffle furnace at a heating rate of 5°C / min and calcined for 4 h to obtain a carrier.

[0210] (2) Weigh 73.973g Ni(NO3)2·6H2O and divide it into two parts, the first part is 55% Ni(NO3)2·6H2O and the second part is 45% Ni(NO3)2·6H2O. Weigh 24.298g Cu(NO3)2·3H2O and divide it into two parts, the first part is 55% Cu(NO3)2·3H2O and the second part is 45% Cu(NO3)2·3H2O. Prepare 56mL of aqueous solution of the first part Ni(NO3)2·6H2O and the first part Cu(NO3)2·3H2O, and then impregnate it on the support obtained in step 1). After the first impregnation, dry it in an oven at 50°C for 3h, then dry it at 105°C for 5h, and finally calcine it in a muffle furnace at 530°C for 5h to obtain a first impregnation catalyst. After obtaining the first impregnation catalyst, start the second impregnation, and mix the second part Ni(NO3)2·6H2O and the second part Cu(NO3)2·3H2O. Cu(NO3)2·3H2O was prepared into 56mL of aqueous solution, and then impregnated onto the first impregnation catalyst. After the second impregnation, it was first dried in an oven at 50°C for 3h, then dried at 105°C for 5h, and finally calcined in a muffle furnace at 530°C for 5h to obtain a hydrogenation catalyst. The content of each component was: CuO content 8wt%, NiO content 19wt%, CeO2 content 1.5wt%, Al2O3 content 69.5wt%, and TiO2 content 2wt%.

[0211] Catalyst Evaluation:

[0212] The catalyst prepared in Example 6 was used and the catalyst evaluation method was the same as that in Example 1. The results are shown in Table 6 below.

[0213] Table 6 Hydrogenation results of the catalyst of Example 6 on different raw materials

[0214]

[0215] Example 7

[0216] Catalyst preparation:

[0217] The preparation method is the same as that of Examples 5 and 6, but the contents of NiO and Al2O3 in the catalyst are adjusted.

[0218] (1) 84.67 g of pseudo-boehmite (dry basis 75%), 2.451 g of metatitanic acid, 1.5 g of CeO2 and 2.659 g of sesbania powder were mixed evenly, and then 50 mL of a mixed acid solution containing 0.886 g of citric acid and 1.772 g of HNO3 (65%) was added and mixed evenly. The mixture was formed on an extruder, dried at 90°C for 3 h, and then dried at 110°C for 3 h. The mixture was then heated to 530°C in a muffle furnace at a heating rate of 5°C / min and calcined for 4 h to obtain a carrier.

[0219] (2) Weigh 97.332g Ni(NO3)2·6H2O and divide it into two parts, the first part is 55% Ni(NO3)2·6H2O and the second part is 45% Ni(NO3)2·6H2O. Weigh 24.298g Cu(NO3)2·3H2O and divide it into two parts, the first part is 55% Cu(NO3)2·3H2O and the second part is 45% Cu(NO3)2·3H2O. Prepare 53mL of aqueous solution of the first part Ni(NO3)2·6H2O and the first part Cu(NO3)2·3H2O, and then impregnate it on the support obtained in step 1). After the first impregnation, dry it in an oven at 50°C for 3h, then dry it at 105°C for 5h, and finally calcine it in a muffle furnace at 530°C for 5h to obtain a first impregnation catalyst. After obtaining the first impregnation catalyst, start the second impregnation, and mix the second part Ni(NO3)2·6H2O and the second part Cu(NO3)2·3H2O. Cu(NO3)2·3H2O was prepared into 53mL of aqueous solution, and then impregnated onto the first impregnation catalyst. After the second impregnation, it was first dried in an oven at 50°C for 3h, then dried at 105°C for 5h, and finally calcined in a muffle furnace at 530°C for 5h to obtain a hydrogenation catalyst. The content of each component was: CuO content 8wt%, NiO content 25wt%, CeO2 content 1.5wt%, Al2O3 content 63.5wt%, and TiO2 content 2wt%.

[0220] Catalyst Evaluation:

[0221] The catalyst prepared in Example 7 was used and the catalyst evaluation method was the same as that in Example 1. The results are shown in Table 7 below.

[0222] Table 7 Hydrogenation results of the catalyst of Example 7 on different raw materials

[0223]

[0224] Example 8

[0225] Catalyst preparation:

[0226] The preparation method is the same as that of Example 1, but the contents of CeO2 and Al2O3 in the catalyst are adjusted.

[0227] (1) 88 g of pseudo-boehmite (dry basis 75%), 1.226 g of metatitanic acid, 4.0 g of CeO2 and 2.798 g of sesbania powder were mixed evenly, and then 53 mL of a mixed acid solution containing 0.932 g of citric acid and 1.865 g of HNO3 (65%) was added and mixed evenly. The mixture was formed on an extruder, dried at 90°C for 3 h, and then dried at 110°C for 3 h. The mixture was then heated to 550°C in a muffle furnace at a heating rate of 5°C / min and calcined for 4 h to obtain a carrier.

[0228] (2) Weigh 81.759g Ni(NO3)2·6H2O and divide it into two parts. The first part contains 55% Ni(NO3)2·6H2O and the second part contains 45% Ni(NO3)2·6H2O. Weigh 24.298g Cu(NO3)2·3H2O and divide it into two parts. The first part contains 55% Cu(NO3)2·3H2O and the second part contains 45% Cu(NO3)2·3H2O. The first portion of Ni(NO3)2·6H2O and the first portion of Cu(NO3)2·3H2O are prepared into 52mL of aqueous solution, and then impregnated onto the carrier obtained in step 1). After the first impregnation is completed, they are first dried in an oven at 50°C for 3h, then dried at 105°C for 5h, and finally calcined at 530°C in a muffle furnace for 5h to obtain a first impregnation catalyst; after obtaining the first impregnation catalyst, the second impregnation is started, the second portion of Ni(NO3)2·6H2O and the second portion of Cu(NO3)2·3H2O are prepared into 52mL of aqueous solution, and then impregnated onto the first impregnation catalyst. After the second impregnation is completed, they are first dried in an oven at 50°C for 3h, then dried at 105°C for 5h, and finally calcined at 530°C in a muffle furnace for 5h to obtain a hydrogenation catalyst, wherein the contents of each component are: CuO content 8wt%, NiO content 21wt%, CeO2 content 4wt%, Al2O3 content 66wt%, and TiO2 content 1wt%.

[0229] Catalyst Evaluation:

[0230] The catalyst prepared in Example 8 was used, and the catalyst evaluation method was the same as that in Example 1. The results are shown in Table 8 below.

[0231] Table 8 Hydrogenation results of the catalyst of Example 8 on different raw materials

[0232]

[0233] Implementation Benefits

[0234] Catalyst preparation:

[0235] Compared with Example 1, the contents of the components in the catalyst are the same, and the calcination temperature of the catalyst in step 2 is adjusted to 490°C.

[0236] Catalyst Evaluation:

[0237] The catalyst prepared in Example 9 was used and the catalyst evaluation method was the same as that in Example 1. The results are shown in Table 9 below.

[0238] Table 9 Hydrogenation results of the catalyst of Example 9 on different raw materials

[0239]

[0240] Example 10

[0241] Catalyst preparation:

[0242] Compared with Example 1, the contents of the components in the catalyst are the same, and the calcination temperature of the catalyst in step 2 is adjusted to 545°C.

[0243] Catalyst Evaluation:

[0244] The catalyst prepared in Example 10 was used, and the catalyst evaluation method was the same as that in Example 1. The results are shown in Table 10 below.

[0245] Table 10 Hydrogenation results of the catalyst of Example 10 on different raw materials

[0246]

[0247] Embodiment 11

[0248] Catalyst preparation:

[0249] Compared with Example 1, the Cu source for preparing the catalyst was partially replaced by copper acetate, and the content of each component in the catalyst remained unchanged, specifically:

[0250] (1) 91.33 g of pseudo-boehmite (dry basis 75%), 1.226 g of metatitanic acid, 1.5 g of CeO2 and 2.822 g of sesbania powder were mixed evenly, and then 53 mL of a mixed acid solution containing 0.941 g of citric acid and 1.881 g of HNO3 (65%) was added and mixed evenly. The mixture was formed on an extruder, dried at 90°C for 3 h, and then dried at 110°C for 3 h. The mixture was then heated to 550°C in a muffle furnace at a heating rate of 5°C / min and calcined for 4 h to obtain a carrier.

[0251] (2) Weigh 81.759g Ni(NO3)2·6H2O and divide it into two portions, the first portion containing 55% Ni(NO3)2·6H2O and the second portion containing 45% Ni(NO3)2·6H2O. Weigh 20.667g Cu(NO3)2·3H2O and divide it into two portions, the first portion containing 55% Cu(NO3)2·3H2O and the second portion containing 45% Cu(NO3)2·3H2O. Weigh 3g copper acetate monohydrate (Cu(CO2CH3)2·H2O) and divide it into two portions, the first portion containing 55% copper acetate monohydrate and the second portion containing 45% copper acetate monohydrate. The first portion of Ni(NO3)2·6H2O, the first portion of Cu(NO3)2·3H2O and the first portion of copper acetate monohydrate are prepared into a 52 mL aqueous solution, and then impregnated onto the carrier obtained in step 1). After the first impregnation, the catalyst is dried at 50°C for 3 h in an oven, then dried at 105°C for 5 h, and finally calcined at 530°C for 5 h in a muffle furnace to obtain a first impregnation catalyst. After obtaining the first impregnation catalyst, the second impregnation is started, and the second portion of Ni(NO3)2·6H2O, the second portion of Cu(NO3)2·3H2O and the first portion of copper acetate monohydrate are prepared into a 52 mL aqueous solution, and then impregnated onto the carrier obtained in step 1). After the first impregnation is completed, the catalyst is dried at 50°C for 3 h in an oven, then dried at 105°C for 5 h, and finally calcined at 530°C for 5 h in a muffle furnace to obtain a first impregnation catalyst. After obtaining the first impregnation catalyst, the second impregnation is started, and the second portion of Ni(NO3)2·6H2O, the second portion of Cu(NO3)2·3H2O and the first portion of Cu(NO3)2·3H2O are prepared into a 52 mL aqueous solution, and then impregnated onto the carrier obtained in step 1). Cu(NO3)2·3H2O and the second portion of copper acetate monohydrate were prepared into a 52mL aqueous solution, which was then impregnated onto the once impregnated catalyst. After the second impregnation, it was first dried in an oven at 50°C for 3h, then dried at 105°C for 5h, and finally calcined in a muffle furnace at 530°C for 5h to obtain a hydrogenation catalyst. The contents of each component were: CuO content 8wt%, NiO content 21wt%, CeO2 content 1.5wt%, Al2O3 content 68.5wt%, and TiO2 content 1wt%.

[0252] Catalyst Evaluation:

[0253] The catalyst prepared in Example 11 was used, and the catalyst evaluation method was the same as that in Example 1. The results are shown in Table 11 below.

[0254] Table 11 Hydrogenation results of the catalyst of Example 11 on different raw materials

[0255]

[0256] Example 12

[0257] Catalyst preparation:

[0258] Compared with Example 1, the Ni source for preparing the catalyst was partially replaced by nickel acetate, and the content of each component in the catalyst remained unchanged, specifically:

[0259] (1) 91.33 g of pseudo-boehmite (dry basis 75%), 1.226 g of metatitanic acid, 1.5 g of CeO2 and 2.822 g of sesbania powder were mixed evenly, and then 53 mL of a mixed acid solution containing 0.941 g of citric acid and 1.881 g of HNO3 (65%) was added and mixed evenly. The mixture was formed on an extruder, dried at 90°C for 3 h, and then dried at 110°C for 3 h. The mixture was then heated to 550°C in a muffle furnace at a heating rate of 5°C / min and calcined for 4 h to obtain a carrier.

[0260] (2) Weigh 74.748g Ni(NO3)2·6H2O and divide it into two parts, the first part accounts for 55% Ni(NO3)2·6H2O and the second part accounts for 45% Ni(NO3)2·6H2O. Weigh 6g nickel acetate tetrahydrate (C4H6O4Ni·4H2O) and divide it into two parts, the first part accounts for 55% nickel acetate tetrahydrate and the second part accounts for 45%. Weigh 24.298g Cu(NO3)2·3H2O and divide it into two parts, the first part accounts for 55% Cu(NO3)2·3H2O and the second part accounts for 45%. The first portion of Ni(NO3)2·6H2O, the first portion of nickel acetate tetrahydrate and the first portion of Cu(NO3)2·3H2O were prepared into a 52 mL aqueous solution, and then impregnated onto the carrier obtained in step 1). After the first impregnation, the catalyst was dried at 50°C for 3 h in an oven, then dried at 105°C for 5 h, and finally calcined at 530°C for 5 h in a muffle furnace to obtain a first impregnation catalyst. After obtaining the first impregnation catalyst, the second impregnation was started, and the second portion of Ni(NO3)2·6H2O, the second portion of Nickel acetate tetrahydrate and a second portion of Cu(NO3)2·3H2O were prepared into 52 mL of aqueous solution, and then impregnated onto the once impregnated catalyst. After the second impregnation, it was first dried in an oven at 50°C for 3 h, then dried at 105°C for 5 h, and finally calcined in a muffle furnace at 530°C for 5 h to obtain a hydrogenation catalyst. The contents of each component were: CuO content 8wt%, NiO content 21wt%, CeO2 content 1.5wt%, Al2O3 content 68.5wt%, and TiO2 content 1wt%.

[0261] Catalyst Evaluation:

[0262] The catalyst prepared in Example 12 was used and the catalyst evaluation method was the same as that in Example 1. The results are shown in Table 12 below.

[0263] Table 12 Hydrogenation results of the catalyst of Example 12 on different raw materials

[0264]

[0265] Comparative Example 1

[0266] Catalyst preparation:

[0267] Compared with Example 1, the preparation method is the same, and the content of CuO and Al2O3 in the catalyst is adjusted. Specifically, the content of each component in the catalyst after adjustment is: CuO content 3wt%, NiO content 21wt%, CeO2 content 1.5wt%, Al2O3 content is 73.5wt%, and TiO2 content is 1wt%.

[0268] Catalyst Evaluation:

[0269] The catalyst prepared in Comparative Example 1 was used, and the catalyst evaluation method was the same as that of Example 1. The results are shown in Table 13 below.

[0270] Table 13 Hydrogenation results of the catalyst of Comparative Example 1 on different raw materials

[0271]

[0272] Comparative Example 2

[0273] Catalyst preparation:

[0274] Compared with Example 1, the preparation method is the same, and the content of NiO and Al2O3 in the catalyst is adjusted. Specifically, the content of each component in the catalyst after adjustment is: CuO content 8wt%, NiO content 11wt%, CeO2 content 1.5wt%, Al2O3 content 78.5wt%, and TiO2 content 1wt%.

[0275] Catalyst Evaluation:

[0276] The catalyst prepared in Comparative Example 2 was used, and the catalyst evaluation method was the same as that of Example 1. The results are shown in Table 14 below.

[0277] Table 14 Hydrogenation results of the catalyst of comparative example 2 on different raw materials

[0278]

[0279] Comparative Example 3

[0280] Catalyst preparation:

[0281] Compared with Example 1, the preparation method is the same, and the contents of TiO2 and Al2O3 in the catalyst are adjusted. Specifically, the contents of each component in the catalyst after adjustment are: CuO content 8wt%, NiO content 21wt%, CeO2 content 1.5wt%, Al2O3 content 69.5wt%, and TiO2 content 0wt%.

[0282] Catalyst Evaluation:

[0283] The catalyst prepared in Comparative Example 3 was used, and the catalyst evaluation method was the same as that of Example 1. The results are shown in Table 15 below.

[0284] Table 15 Hydrogenation results of the catalyst of comparative example 3 on different raw materials

[0285]

[0286] Comparative Example 4

[0287] Catalyst preparation:

[0288] Compared with Example 1, the preparation method is the same, and the contents of CeO2 and Al2O3 in the catalyst are adjusted. Specifically, the contents of each component in the catalyst after adjustment are: CuO content 8wt%, NiO content 21wt%, CeO2 content 0wt%, Al2O3 content 70wt%, and TiO2 content 1wt%.

[0289] Catalyst Evaluation:

[0290] The catalyst prepared in Comparative Example 4 was used, and the catalyst evaluation method was the same as that of Example 1. The results are shown in Table 16 below.

[0291] Table 16 Hydrogenation results of the catalyst of comparative example 4 on different raw materials

[0292]

[0293] Comparative Example 5

[0294] Catalyst preparation:

[0295] Compared with Example 1, the contents of the components in the catalyst are the same, but the preparation method is different. Specifically, the calcination temperature of the catalyst in step 2 is 390°C.

[0296] Catalyst Evaluation:

[0297] The catalyst prepared in Comparative Example 5 was used, and the catalyst evaluation method was the same as that of Example 1. The results are shown in Table 17 below.

[0298] Table 17 Hydrogenation results of the catalyst of comparative example 5 on different raw materials

[0299]

[0300] It can be seen from the examples that the catalyst prepared by the present invention has a high hydrogenation performance and can be applied to the hydrogenation of various materials, especially suitable for the hydrogenation reaction of carbon-carbon double bonds and / or carbon-oxygen double bonds.

[0301] The above is a detailed introduction to a multi-purpose hydrogenation catalyst provided by the present invention, its preparation method and application. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method and its core ideas of the present invention, including the best mode, and also enables any technician in the field to practice the present invention, including the manufacture and use of any device or system, and the implementation of any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A hydrogenation catalyst, characterized in that The hydrogenation catalyst is composed of copper oxide, nickel oxide, cerium oxide, titanium oxide and aluminum oxide; In the hydrogenation catalyst, the mass content of copper oxide is 8% to 25%; The mass content of nickel oxide is 19% to 30%; The mass content of cerium oxide is 1% to 5%; The mass content of titanium oxide is 1% to 5%; The mass content of aluminum oxide is 35% to 71%.

2. The hydrogenation catalyst according to claim 1, characterized in that The hydrogenation catalyst is a hydrogenation catalyst used for hydrogenation of carbon-carbon double bonds and / or hydrogenation of carbon-oxygen double bonds; The hydrogenation catalyst specifically comprises a carrier composed of aluminum oxide and titanium oxide, and main active components of nickel oxide and copper oxide, and a secondary active component of cerium oxide, which are composited on the carrier; The carrier comprises a porous carrier; The hydrogenation catalyst is a hydrogenation catalyst that needs to be reduced and activated before use.

3. A method for preparing a hydrogenation catalyst according to any one of claims 1 to 2, characterized in that: The following steps are involved: 1) mixing an aluminum source, a titanium source, a cerium source, an additive and an acid solution, and forming, drying and calcining to obtain a carrier; 2) premixing a portion of the copper source, a portion of the nickel source and water to obtain a first mixed solution, and then placing the carrier obtained in the above step in the first mixed solution for a first impregnation, and then performing a first calcination to obtain a semi-finished product; 3) The remaining copper source, the remaining nickel source and water are mixed again to obtain a second mixed solution, and the semi-finished product obtained in the above steps is placed in the second mixed solution for a second impregnation, and then calcined for a second time to obtain a hydrogenation catalyst.

4. The preparation method according to claim 3, characterized in that: The aluminum source is selected from pseudo-boehmite and / or aluminum hydroxide dry gel; The titanium source is selected from metatitanic acid and / or TiO2; The cerium source is selected from cerium oxide; The auxiliary agent is selected from sesbania powder; The acid is selected from one or more of nitric acid, citric acid and malic acid.

5. The preparation method according to claim 3, characterized in that: The additive is added in an amount of 1.5% to 5.5% of the total mass of the aluminum source, the cerium source and the titanium source; The amount of the acid added is 0.05% to 7.5% of the total mass of the aluminum source, the cerium source and the titanium source; The specific steps of the mixing are: firstly mixing the aluminum source, the titanium source, the cerium source and the auxiliary agent, and then adding the acid solution to continue mixing; In the step 1), the heating rate of the calcination is 2 to 5°C / min; In the step 1), the calcination temperature is 470-580°C; In the step 1), the calcination time is 2 to 9 hours.

6. The preparation method according to claim 3, characterized in that: The specific process of drying in step 1) is: drying at 60-80°C for 1-3 hours, and then drying at 105-120°C for 3-9 hours; The heating rate of the first calcination is 2-5°C / min; The temperature of the first calcination is 400-560°C; The first calcination time is 2 to 8 hours.

7. The preparation method according to claim 3, characterized in that: The copper source is selected from copper nitrate and / or copper acetate; The nickel source is selected from nickel nitrate and / or nickel acetate; The mass of the portion of the copper source accounts for 0.1% to 70% of the total mass of the copper source; The mass of the part of nickel source accounts for 0.1% to 70% of the total mass of the nickel source; The method further comprises a drying step before the first calcination and / or before the second calcination.

8. The preparation method according to claim 7, characterized in that: The specific drying process before the first calcination and the second calcination is independently selected from: drying at 40-80°C for 1-10 hours, and then drying at 105-125°C for 3-5 hours; The heating rate of the second calcination is 2-5°C / min; The temperature of the second calcination is 400-560°C; The second calcination time is 2 to 8 hours.

9. Use of the hydrogenation catalyst according to any one of claims 1 to 2 or the hydrogenation catalyst prepared by the preparation method according to any one of claims 3 to 8 as a hydrogenation catalyst in the process of carbon-carbon double bond hydrogenation and / or carbon-oxygen double bond hydrogenation.

10. The use according to claim 9, characterized in that: The application is specifically to firstly reduce and activate the hydrogenation catalyst, and then perform the hydrogenation catalytic process; The reduction activation method includes performing reduction activation under hydrogen conditions; The volume ratio of hydrogen to hydrogenation catalyst is (100-2000) mL / h:1 mL; The reduction activation temperature is 150-470°C; The reduction activation time is 4 to 46 hours; The heating rate of the reduction activation is 1-10°C / min.

Citation Information

Patent Citations

  • Olefin hydrogenation catalyst and preparation method and application thereof

    CN112547114A

  • Method for preparing n-propyl alcohol by catalyzing propionaldehyde hydrogenation with nickel-based catalyst

    CN113713817A

Cited By

  • Hydrogenation catalyst and preparation method thereof

    CN121467105A